Juridical analysis of legal protection for children as criminal offenders according to the law on juvenile justice system - Qurba, Harry; Faturohman, Faturohman (Institute Of computer Science (IOCS), 2025)
Legal protection for children who are perpetrators of criminal acts is in accordance with Law Number 11 of 2012 concerning the Child Criminal Justice System (SPPA). Children as perpetrators of criminal acts require special treatment due to their immature status legally and psychologically. The main objective of the SPPA Law is to ensure that the legal process against children is carried out with the principles of restorative justice and a diversion approach, so as to minimize the negative impact on the child's future. The research method used is the normative juridical method, with a legislative approach and case analysis. The results showed that the SPPA Law provides legal protection to children through diversion mechanisms at every stage of the judicial process, restrictions on sentencing, and the obligation to involve Bapas (Correctional Center) in the judicial process. However, in its implementation, there are still challenges such as the lack of understanding of law enforcement officials on the concept of restorative justice and limited supporting facilities. In conclusion, legal protection for child offenders has been comprehensively regulated in the SPPA Law, but it requires capacity building of law enforcement officials and infrastructure support to optimize the implementation of restorative justice. Thus, the rights of children as individuals who require special protection can be guaranteed and maximally accommodated. The solution implemented is the restructuring of child protection laws to be more specific in handling them